Toxic gamers: Studi fenomenologis terhadap perilaku kekerasan verbal pada siswa pemain game online - Ariffudin, Imam (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to reveal the psychological dynamics of students who commit verbal violence while playing online games. A qualitative study with a phenomenological design was used as the basis for conducting the study. Data were collected using observation techniques and in-depth interviews with six students of SMPN 10 Surabaya. The collected data were then coded and analyzed using thematic analysis. The results of the study showed that psychological experiences: catharsis and locus of control were the main themes most often raised by students. In addition, the results of the analysis also showed that low emotional regulation and self-control skills triggered the emergence of toxic behavior in students. Based on these findings, it can be concluded that catharsis and locus of control are factors causing the emergence of verbal violence in students playing online games.